Solution of an initial-value problem for parabolic equations via monotone operator methods - Vincenzo La Rosa; Calogero Vetro (Electronic Journal of Differential Equations, 2014)
We study a general initial-value problem for parabolic equations in Banach spaces, by using a monotone operator method. We provide sufficient conditions for the existence of solution to such problem.